Constitutional Guarantees for Achieving Criminal Justice: A Study of Libyan Constitutional Documents (1951-2011) - Fawzi Ibrahim Diab (International Journal of Law Research and Studies, 2025)
The constitution includes mandatory higher rules that are superior to other legal rules; therefore, we find a close connection between its rules and the rules of criminal law in its two parts (crimes and penalties), because the latter represents a danger to the human rights system from the ruling with penalties that deprive freedom and confiscate the right of individuals to life; therefore, most countries are keen to establish constitutional criminal legitimacy through the texts of their constitutions, and to establish a number of principles and foundations that would provide guarantees that contribute to achieving criminal justice. The importance of the research is evident in shedding light on the constitutional criminal rules that contribute to achieving criminal justice, and stating the constitutional guarantees that would protect the rights and freedoms of individuals through studying the Libyan constitutional documents during the period (1951 - 2011). The study raises a number of problems, the most important of which are: To what extent do constitutional documents in Libya include guarantees that had an impact on achieving criminal justice? The subject is studied through two requirements, the first of which deals with the basic constitutional guarantees in terms of stating the principles of criminal legitimacy and the principles of fair trial, while the second requirement deals with the supporting constitutional guarantees, which are represented in the principle of the supremacy of the constitution and oversight of the constitutionality of laws.